Two new isoxazolines from the husks of Xanthoceras sorbifolia Bunge. Issue 8 (2nd August 2016) - Ge, Hui-Qi; Wan, Guo-Sheng; Wang, Da; Wu, Ji-Ming; Sun, Bo-Hang; Wu, Li-Jun; Gao, Hui-Yuan
Abstract: Two new isoxazoline compounds, 1-oxa-2-azaspiro[4.5]dec-2-ene-8 β -ol (1 ) and 1-oxa-2-azaspiro[4.5]dec-2-ene-8 α -ol (2 ), were isolated from the husks of fruits of Xanthoceras sorbifolia Bunge and their structures were determined by spectroscopic analyses, including X-ray crystallography, HRESI-MS, UV, IR, and 1D and 2D NMR (HSQC, HMBC, NOESY) methods. Neither compound showed significant inhibitory effects on butyrylcholinesterase (BuchE) and acetylcholinesterase (AChE), nor the selected tumor cells growth. Based on an online activity prediction program (PASS ONLINE), the structures with isoxazoline skeletons were found to show potential anti-asthmatic (AM) and anti-anaphylaxis (AP) activities; moreover, compounds1 and2 were predicted to possess high affinities for many enzymes involved in AM and AP according to the RCSB Protein Data Bank. High-affinity binding to phosphodiesterase IV (PDE-4), an important inflammatory modulator in asthma, was demonstrated experimentally, beside that, the predicted structures based on compounds1 and2 were analyzed for PDE-4 interactions using the molecular docking methodology of Discovery Studio 3.0 (DS 3.0). The predicted structure2A-6 exhibited much higher affinity and stability of PDE-4 binding than the clinical PDE-4 inhibitor rolipram.